Austria's Potential for Trade in Services - V. Brandicourt; C. Schwellnus; Julia Woerz (FIW - Research Centre International Economics, 2008)
We estimate the potential for trade in services in a 2-step approach using a gravity model for a sample of bilateral service trade flows in individual service categories between 65 countries over the period 2000 to 2005. In particular, we focus on the Austrian economy's potential for untapped trade in services which appears to be substantial. While Austria's travel services are reaching their potential, there is still ample room for exports of commercial services. Our analysis further points to the fact that this lack of exploiting the potential arises less from legal and institutional features as measured by OECD regulation indicators, but rather from other structural features of the Austrian economy.
Keywords: F14; 330; export of services; trade in services; commercial services; gravity modelling; regulation